High‐Rate and Long Cycle‐Life Alloy‐Type Magnesium‐Ion Battery Anode Enabled Through (De)magnesiation‐Induced Near‐Room‐Temperature Solid–Liquid Phase Transformation. Issue 45 (25th October 2019) - Wang, Lin; Welborn, Samuel S.; Kumar, Hemant; Li, Manni; Wang, Zeyu; Shenoy, Vivek B.; Detsi, Eric
Abstract: Resources used in lithium‐ion batteries are becoming more expensive due to their high demand, and the global cobalt market heavily depends on supplies from countries with high geopolitical risks. Alternative battery technologies including magnesium‐ion batteries are therefore desirable. Progress toward practical magnesium‐ion batteries are impeded by an absence of suitable anodes that can operate with conventional electrolyte solvents. Although alloy‐type magnesium‐ion battery anodes are compatible with common electrolyte solvents, they suffer from severe failure associated with huge volume changes during cycling. Consequently, achieving more than 200 cycles in alloy‐type magnesium‐ion battery anodes remains a challenge. Here an unprecedented long‐cycle life of 1000 cycles, achieved at a relatively high (dis)charge rate of 3 C (current density: 922.5 mA g −1 ) in Mg2 Ga5 alloy‐type anode, taking advantage of near‐room‐temperatures solid–liquid phase transformation between Mg2 Ga5 (solid) and Ga (liquid), is demonstrated. This concept should open the way to the development of practical anodes for next‐generation magnesium‐ion batteries. Abstract : Here an unprecedented long‐cycle life of 1000 cycles is demonstrated, achieved at a relatively high (dis)charge rate of 3 C (current density: 922.5 mA g −1 ) in Mg2 Ga5 alloy‐type anode, taking advantage of near‐room‐temperatures solid–liquid phase transformations between Ga(liquid) and Mg2 Ga5 (solid). This concept should open the way to the development of practical anodes for next‐generation magnesium‐ion batteries.